Magneto-optical traps on a chip using micro-fabricated gratings - Nshii, C.; Vangeleyn, M.; Cotter, J.; Griffin, P.; Ironside, Charlie; See, P.; Sinclair, A.; Hinds, E.; Riis, E.; Arnold, A. (2013)
We have made magneto-optical traps (MOTs) on a chip which is able to cool and trap ~108 atoms directly from a ~1cm3 thermal background of 87Rb. Diffraction gratings are used to manipulate the light from a single input beam to create the beams required for a MOT [1,2]. The gratings are etched into the surface of a silicon or GaAs wafer by either electron beam, or photo-lithography making them simple to fabricate and integrate into other atom chip architectures. We have developed a variety of gratings for utilisation both inside and outside a vacuum chamber - facilitating their incorporation into both new and existing devices. Unlike previously integrated cold atom sources on a chip [3,4] the atoms now sit above the surface where they can be easily imaged, manipulated and transferred into other on-chip potentials.